Comparisons of Effective Fields of Two Ultra-Widefield Ophthalmoscopes, Optos 200Tx and Clarus 500. (5th December 2019) - Matsui, Yoshitsugu; Ichio, Atsushi; Sugawara, Asako; Uchiyama, Eriko; Suimon, Hitomi; Matsubara, Hisashi; Sugimoto, Masahiko; Ikesugi, Kengo; Kondo, Mineo
Abstract : Purpose . To compare the effective fields of the Optos 200Tx® and Clarus 500™, two ultra-widefield ophthalmoscopes, based on their ability to image branches of retinal vessel in the four retinal quadrants. Methods . Ninety retinal images from 90 patients with various eye diseases were studied. All patients had undergone 200° retinal imaging to obtain a single image of Optos (O) and the montage of two images of the Clarus (C). The highest number of traceable vessel branches in the four retinal quadrants was determined by two masked raters. An image was classified as "O > C" when the number of identifiable branch was greater in the Optos than the Clarus, as "O = C" when the number was equal and as "O < C" when the number was fewer in the Optos than the Clarus. Results . The appearance probability of "O > C" was significantly higher at the upper temporal quadrant than "O < C" (p < 0.01 for both raters). In contrast, the appearance probability of "O < C" was significantly higher at the lower nasal quadrant than "O > C" (p < 0.01 for both raters). There were no significant differences in the appearance probability between "O > C" and "O < C" at the other two retinal quadrants (p > 0.50 for both raters). Conclusions . These results demonstrate that the effective field of views was different between the two devices at different retina quadrants. Further studies are needed to clarify possible factors such as artifacts by the eyelashes, differences in the depth of focus, motion of the device, and different locations of the images on the effective field of views.